Elucidating Decorin's role in the preovulatory follicle - A. Kedem; K. Ulanenko-Shenkar; Y. Yung; G. M. Yerushalmi; E. Maman; A. Hourvitz (BMC, 2020)
Abstract Background DCN (decorin) is a proteoglycan known to be involved in regulating cell proliferation, collagen fibril organization and migration. In our global transcriptome RNA-sequencing approach to systematically identify new ovulation-associated genes, DCN was identified as one of the highly regulated genes. We therefore hypothesize that DCN may have a role in ovulatory processes such as cell migration and proliferation. Aim To characterize the expression, regulation and function of the proteoglycan DCN in the human ovarian follicles during the preovulatory period. Methods The in-vivo expression of DCN mRNA in mural (MGCs) and cumulus (CGCs) granulosa cells was characterized using quantitative RT-PCR and western blot. A signaling study was performed by treating human MGCs cultures with gonadotropins and different stimulators and inhibitors to determine their effect on DCN expression by qRT- PCR and elucidate the pathways regulating these proteins. In a functional study, KGN granulosa cell line was used to study cell migration with a scratch assay. Results DCN mRNA expression was significantly higher in MGCs compared to CGCs. DCN mRNA was significantly higher in CGCs surrounding mature metaphase II (MII) oocytes compared to CGCs of germinal vesicle (GV) and metaphase I (MI) oocytes. hCG significantly increased DCN mRNA and protein expression levels in cultured MGCs. Using signal transduction activators and inhibitors, we demonstrated that DCN induction by LH/hCG is carried out via PKA, PKC, ERK/MEK, and PI3K pathways. We showed that DCN expression is also induced in high-density cell cultures, in a dose-dependent pattern. In addition, progesterone induced a significant increase in DCN secretion to the media. MGCs from follicles of endometriosis patients exhibited reduced (about 20% of) mRNA transcriptions levels compared to MGCs follicles of control patients. More significantly, we found that DCN has an inhibiting effect on KGN cell migration. Conclusions Our study indicates that DCN is a unique ovulatory gene. Our findings support the hypothesis that DCN plays an important new role during the preovulatory period and ovulation, and stress its involvement in endometriosis infertility. A better understanding of DCN role in ovulation and endometriosis may provide treatment for some types of infertility.